Towards a Circular Economy Through 9R-Based E-waste Management: A Case Study on the Role of Employees in Indonesia's Financial Services Sector - Febe Budianto; Ratna Lindawati Lubis (urn:multiple://2988-7828multiple.v3i84)
This study aims to explore the practices of electronic waste (e-waste) management in the Indonesian banking sector within the framework of the circular economy based on the principles of Refuse, Rethink, Reduce, Reuse, Repair, Refurbish, Remanufacture, Repurpose, and Recycle (9R), as well as to understand the role and challenges of integrating the informal sector into the management system. This research adopts a qualitative case study approach, using in-depth interviews with six informants from large and small banks. The findings reveal that large banks tend to implement formal and systematic policies, while small banks rely on informal initiatives such as reuse and refurbish. Additionally, the informal sector plays a crucial role in collection and recycling but faces structural barriers to formalization. The limitations of this study include the restricted geographic scope and descriptive approach. Therefore, future research is recommended to employ a quantitative method and cover a broader range of regions and actors. From a practical perspective, more inclusive policies are needed to support the integration of the informal sector into a sustainable formal e-waste management system.